Candi Sukuh dan Representasi Agensi: Simbolisme, Ritual, dan Identitas Sosial pada Masa Akhir Majapahit: Candi Sukuh dan representasi agensi: Simbolisme, ritual, dan identitas sosial pada masa akhir Majapahit - Harriyadi (Berkala Arkeologi, 2025)
Sukuh Temple is a Hindu worship site from the Late Majapahit period, and its artifacts represent distinct characteristics that contrast with the socio-cultural system of Majapahit. This study aims to explain the formation of socio-cultural identity due to the dialectical relationship between agents and structure, which leads to cultural reproduction. The research applies Anthony Giddens’ structuration theory. Data were collected from the archaeological remains at Candi Sukuh and relevant studies. Contextual analysis was conducted to understand the relationships and chronology of various events. The findings, through the application of structuration theory, indicate that political instability and the rise of Karesian in the Late Majapahit era led to the emergence of a community that supported Candi Sukuh’s cultural traditions. The practice of rituals and interactions among community members resulted in socio-cultural reproduction. As a consequence, a distinctive group identity was formed and is represented in the artifacts of Candi Sukuh.